A Nanoscale Multiresponsive Luminescent Sensor Based on a Terbium(III) Metal–Organic Framework. Issue 8 (1st July 2015) - Dang, Song; Wang, Ting; Yi, Feiyan; Liu, Qinghui; Yang, Weiting; Sun, Zhong‐Ming
Abstract A nanoscale terbium‐containing metal–organic framework (nTbL), with a layer‐like structure and [H2NMe2]+ cations located in the framework channels, was synthesized under hydrothermal conditions. The structure of the as‐prepared sample was systematically confirmed by powder XRD and elemental analysis; the morphology was characterized by field‐emission SEM and TEM. The photoluminescence studies revealed that rod‐like nTbL exhibited bright‐green emission, corresponding to 5D4→7FJ (J=6–3) transitions of the Tb3+ ion under excitation. Further sensing measurements revealed that as‐prepared nTbL could be utilized as a multiresponsive luminescent sensor, which showed significant and exclusive detection ability for Fe3+ ions and phenylmethanol. These results highlight the practical applications of lanthanide‐containing metal–organic frameworks as fluorescent probes.